2001
DOI: 10.1063/1.1353813
|View full text |Cite
|
Sign up to set email alerts
|

Very-low-specific-resistance Pd/Ag/Au/Ti/Au alloyed ohmic contact to p GaN for high-current devices

Abstract: We report on Pd/Ag/Au/Ti/Au alloyed metallic contact to p GaN. An 800 °C anneal for 1 min in flowing nitrogen ambient produces an excellent ohmic contact with a specific contact resistivity close to 1×10−6 Ω cm2 and with good stability under high current operation conditions. This high-temperature anneal forms an alloy between Ag, Au, and p GaN resulting in a highly p-doped region at the interface. Using x-ray photoelectron spectroscopy and x-ray diffraction analysis, we confirm that the contact formation mech… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
15
0

Year Published

2004
2004
2017
2017

Publication Types

Select...
4
2
1

Relationship

0
7

Authors

Journals

citations
Cited by 44 publications
(17 citation statements)
references
References 18 publications
2
15
0
Order By: Relevance
“…The AES and GXRD results showed that the increase in the annealing temperature above 600 • C leads to indiffusion of Pt, Pd, and Au atoms and formation of the Ga 3 Pt 5 , Ga 2 Pd 5 , and Au 7 Ga 2 phases at the metal/GaN in- terface. This is in good agreement with those previously reported by other groups [19][20][21][22][23][24][25][26][27][28][29]. It is well known that for the Pt-and Pd-based contacts for p-GaN, Pt and Pd readily react with GaN and form Pd-Ga and Pt-Ga related phases upon annealing [19][20][21][22][23][24][25][26][27][28][29].…”
Section: Resultssupporting
confidence: 92%
See 2 more Smart Citations
“…The AES and GXRD results showed that the increase in the annealing temperature above 600 • C leads to indiffusion of Pt, Pd, and Au atoms and formation of the Ga 3 Pt 5 , Ga 2 Pd 5 , and Au 7 Ga 2 phases at the metal/GaN in- terface. This is in good agreement with those previously reported by other groups [19][20][21][22][23][24][25][26][27][28][29]. It is well known that for the Pt-and Pd-based contacts for p-GaN, Pt and Pd readily react with GaN and form Pd-Ga and Pt-Ga related phases upon annealing [19][20][21][22][23][24][25][26][27][28][29].…”
Section: Resultssupporting
confidence: 92%
“…The p-GaN layer was ultrasonically degreased with acetone, methanol, and methanol for 5 min in each step, and then rinsed with deionized water followed by N 2 blowing. The p-GaN layers were then boiled in a buffered hydrofluoric (BHF) solution for 10 min to remove surface oxide layers [29]. For the measurement of contact resistivity, an active region was defined by inductively-coupledplasma reactive ion etching (ICP-RIE) using a mixture of BCl 3 /Cl 2 /Ar gases.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…The surface morphology can become very rough, especially in the case of the common Ni/Au contact, and the contact can fail to display Ohmic properties. A number of approaches to compensate for this problem have been explored, including the use of non-alloyed Rh-based contacts [22] and Pd [23], W [29], as well as families of borides [30,31] and nitrides [32].…”
Section: Introductionmentioning
confidence: 99%
“…The development and fabrication of flip-chip GaN based LEDs has prompted the search for highreflectivity metallizations, in addition to stable, ohmic and low resistivity contact to GaN. There are few researchers who use silver (Ag) or metal/silver as metal contact to n-GaN, and it is rarely used as metal contacts to p-GaN [15], although silver has good electrical resistivity (1.59 × 10 -6 Ωcm) and thermal conductivity (1 cal/cm-s-°C) [16]. Moreover, silver can form electrically superior contacts to p-GaN than Ni/Au, and has higher reflectivity than Al [17].…”
Section: Introductionmentioning
confidence: 99%